Penyalahgunaan Data Pribadi Pasien Dalam Rekam Medis Oleh Tenaga Medis/Tenaga Kesehatan Rumah Sakit - Setiawan, Dion Putra; H, Hufron (Media Hukum Indonesia (MHI), 2024)
Misuse of patient personal data in medical records by medical personnel or health workers in hospitals is a very crucial problem from a legal perspective, because it is directly related to violations of the right to privacy and protection of personal data. Medical records, which contain highly sensitive health information, have strong legal protection at both national and international levels. In Indonesia, Law Number 27 of 2022 concerning Personal Data Protection (UU PDP) provides a legal basis for managing and protecting patient personal data, including medical data. Misuse of data can take the form of unauthorized access, disclosure of data without permission, or use of data for personal interests. This criminal act of misuse of personal data has serious legal impacts, both for the medical personnel concerned and hospitals as health service providers. This research aims to analyze forms of misuse of patient personal data in medical records by medical personnel and health workers, as well as examine the legal implications that arise, including administrative and criminal sanctions in accordance with applicable regulations. Apart from that, this research also discusses preventive measures that can be implemented by hospitals to prevent these violations from occurring, such as implementing an adequate security system and understanding legal obligations regarding the protection of patient personal data.